Pembimbingan Kemampuan Public Speaking pada Organisasi Kesiswaan SMKN 4 Dumai - Rahmi, Hanifatul; Desriyati, Welly; Julanos (Indra Institute Research & Publication, 2022)
Public Speaking is used to convey information to other people, the delivery of this information can be in the form of face-to-face presentations, speeches, meeting activities, MC or informal meetings. Physical education and comprehensive higher education do not fully influence individuals to appear in public. In communicating activities, of course, a strategy is needed so that the message conveyed to the interlocutor can be received and understood properly. The ability to speak in public will be a psychological illness for some people who are not used to speaking in public. Based on the results of observations made, the confidence level of the students of SMK N 4 Dumai is quite good, but the ability to speak in public is still lacking. This can be seen from the lack of student motivation in speaking in front of their friends and the general public. This can be seen when students are asked to come forward, in speaking they still falter because of the lack of mastery of public speaking. This is what motivated our PKM team to conduct public speaking training at SMK N 4 Dumai in order to increase the motivation and confidence of the students to dare to speak in public. The implementation method used in this service is in the form of introduction, guidance, training and practice in public speaking